2020
DOI: 10.1002/slct.202000747
|View full text |Cite
|
Sign up to set email alerts
|

Shape Shifting of Cup Shaped Particles on Growing poly (2‐hydroxy ethyl methacrylate) Brushes by “Grafting From” Approach and Dissipative Particle Dynamics Simulation

Abstract: Controlled bending leading to shape shifted microparticles is indispensable for the targeted biomedical applications including advanced drug/cell delivery and has been one of the major research components in biomedical area for decades. Here, we report the shape-shifting of cup-shaped particles created by electrojetting from a blend of biodegradable polylactide (PLA) and biocompatible co-polymer (poly[methylmethacrylate-co-2-(2-bromopropionyloxy)ethyl methacrylate] (poly(MMA-co-BEMA))) containing ATRP (Atom Tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 68 publications
0
21
0
Order By: Relevance
“…Images of “as-jetted” cup-shaped particles (before brush modification) were also captured for comparison. After surface-initiated ATRP (SIATRP), the enhancement in particle size was clearly evident from both SEM (average size9.8 μm ± 1.6) ,, and TEM images (average size8.3μm ± 1.5); however, the shape of the particles remained almost unaltered as compared to that of “as-jetted” cup particles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Images of “as-jetted” cup-shaped particles (before brush modification) were also captured for comparison. After surface-initiated ATRP (SIATRP), the enhancement in particle size was clearly evident from both SEM (average size9.8 μm ± 1.6) ,, and TEM images (average size8.3μm ± 1.5); however, the shape of the particles remained almost unaltered as compared to that of “as-jetted” cup particles.…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting that brushes present inside the concave surface of cup particles may not significantly contribute to the overall volume of the particles, hence hindering the post-brush size increment. Moreover, preferential brush growth onto the outside surface of cup particles may happen due to less accessibility of the monomer (DMAEMA) and thus the restricted chain growth inside the confined concave surface. , This may lead to an anisotropic distribution of the adsorbed enzyme in the case of cup particles. On the other hand, being a flat geometry, surfaces of the whole disc would be accessible for enzyme immobilization, resulting in an enhanced loading capacity for disc-shaped particles.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the shape shifting process was not only shape driven but also brush selective. The whole shape shifting phenomena was further confirmed by dissipative particle dynamics simulation studies …”
Section: Surface Anisotropymentioning
confidence: 55%
“…Another interesting class of anisotropic patchy particles would be the presence of polymer-brush-modified patches onto the surface of anisotropic/isotropic particles. Recently, various research groups have shown that anisotropy can also be generated onto the particles either by spatioselective attachment of polymer brush or immobilization of polymer brush onto nonspherical (already anisotropic) particles. ,, The brush-modified particles may undergo nonuniform swelling in water, if the selected brush is hydrophilic in nature, thus bringing anisotropy to the system. Moreover, functionality of polymer brushes and their thickness, architectures, geometry of the substrate, etc., are also the crucial factors that directly affect the properties of the modified particle.…”
Section: Surface Anisotropymentioning
confidence: 99%
See 1 more Smart Citation